Removal of Zinc by the Moss Calymperes delessertii Besch - Lee, C. K.; Low, K.S.; Ng, K.H; Yahya, Asmah (Universiti Putra Malaysia Press, 1994)
Studies were conducted to assess the capability of a moss, Calymperes delessertii Besch, to remove zinc from solutions. In the batch experiments, parameters studied included effect of pH and initial zinc concentration on sorption. A series of fixed bed experiments were performed to study the system under dynamic conditions. The bed depth service time (BDST) model proposedn by Hutchins was successfully applied to the system. The fixed bed experiments were also carried out using waste water from a zinc plating factory and results indicated that moss columns could be used in a clean-up system to remove zinc from electroplating waste water.